2020
DOI: 10.1038/s41598-020-74756-9
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive proteomic investigation of infectious and inflammatory changes in late preterm prelabour rupture of membranes

Abstract: Preterm prelabour rupture of membranes beyond the 34th week of gestation (late PPROM) is frequently associated with the risk of the microbial invasion of the amniotic fluid (MIAC) and histological chorioamnionitis (HCA). Hence, we employed a Tandem Mass Tag-based approach to uncover amniotic fluid proteome response to the presence of MIAC and HCA in late PPROM. Protein dysregulation was associated with only five cases in the group of 15 women with confirmed MIAC and HCA. Altogether, 138 amniotic fluid proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In the last two decades, several investigations employed proteomic approaches to explore biomarkers for MIAC/IAI complicated by PPROM or PTL in AF and cervicovaginal fluid samples [18][19][20][38][39][40] . They reported several new proteins, including α1-acid glycoprotein, IGFBP-1, calgranulins, lipocalin-2, myeloperoxidase, neutrophil protein 1-3, as being associated with MIAC/IAI.…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, several investigations employed proteomic approaches to explore biomarkers for MIAC/IAI complicated by PPROM or PTL in AF and cervicovaginal fluid samples [18][19][20][38][39][40] . They reported several new proteins, including α1-acid glycoprotein, IGFBP-1, calgranulins, lipocalin-2, myeloperoxidase, neutrophil protein 1-3, as being associated with MIAC/IAI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous pre-clinical in vivo studies have implicated the protein activation cascade in the pathogenesis of intestinal inflammation and bacterial infection [ 60 , 61 ]. In addition, a recent study using AF samples has shown that regulation of the protein activation cascade is significantly involved in the pathogenesis of late PPROM complicated by both HCA and MIAC [ 62 ]. A recent study using ex vivo phagocytosis assays, and scanning and transmission electron microscopy showed that phagocytosis by AF neutrophils was observed in the amniotic cavity of patients with intra-amniotic infection, suggesting that neutrophil phagocytosis is an important host defense mechanism for killing microbes invading the amniotic cavity [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study of the protein complement of human placental amniochorionic membrane reported the involvement of inflammation, infection, proteolysis and metabolic alterations, with membrane ECM degradation in both pPROM and PROM 29 . A Tandem Mass Tag-based approach to the proteome of the amniotic fluid from amniocentesis of women with late pPROM (between 34 and 37 weeks of gestation) found 138 proteins significantly changed, associated with acute inflammatory response in samples from women with MIAC and HCA 30 . In particular, the upregulated proteins included S100 proteins, histones, secreted neutrophil proteins as well as proteins associated to redox processes, while the downregulated proteins encompassed regulators of inflammatory response, such as thrombospondin-1 30 .…”
Section: Discussionmentioning
confidence: 99%
“…A Tandem Mass Tag-based approach to the proteome of the amniotic fluid from amniocentesis of women with late pPROM (between 34 and 37 weeks of gestation) found 138 proteins significantly changed, associated with acute inflammatory response in samples from women with MIAC and HCA 30 . In particular, the upregulated proteins included S100 proteins, histones, secreted neutrophil proteins as well as proteins associated to redox processes, while the downregulated proteins encompassed regulators of inflammatory response, such as thrombospondin-1 30 . Similar result underlying infection-associated HCA and MIAC in pPROM were obtained from another quantitative shotgun proteomic study on amniotic fluid from amniocentesis 31 .…”
Section: Discussionmentioning
confidence: 99%